Sosialisasi “LITERASI DIGITAL: Membangun Desa Melalui Media Digital” di Desa Tewaowutung, Kabupaten Lembata - Cindy Claudia Tungga; Kristina Salestin Due Rema; Maria Seviana Ririn; Helena Kamila Kolo; Gaspar Hendrikus Wawo Aja; Innosensia E.I.Ndiki Satu; Hendrikus Saku Bouk (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This socialization aims to provide benefits to the community of the importance of social media as social media as information media and media as marketing media to be able to develop and introduce tourism, typical meaning, and potential in the village of Tewaowutung itself. In the community service activities carried out in Teawaowutung Village, the socialization process was carried out in two stages, namely material presentation and discussion which was attended by weaving, culinary, chicken, and pokdarwis UMKM groups. From the results of socialization with material on the understanding of digital literacy, digital media strategies, types of social media, social media as information media, social media as marketing media. Can provide benefits and advantages to the community from promotion through social media. The speaker also made a tik tok for the village so that it could become a promotional media for Tewaowutung village, to introduce tourism in the village and become a product produced by MSMEs in Tewaowutung village.